Living Electronic Music - Emmerson, Simon (Farnham, MD Ashgate, 2007)
Drawing on recent ideas that explore new environments and the changing situations of composition and performance, Simon Emmerson provides a significant contribution to the study of contemporary music, bridging history, aesthetics and the ideas behind evolving performance practices. Whether created in a studio or performed on stage, how does electronic music reflect what is live and living? What is it to perform 'live' in the age of the laptop? Many performer-composers draw upon a 'library' of materials, some created beforehand in a studio, some coded 'on the fly', others 'plundered' from the widest possible range of sources. But others refuse to abandon traditionally 'created and structured' electroacoustic work. Lying behind this maelstrom of activity is the perennial relationship to 'theory', that is, ideas, principles and practices that somehow lie behind composers' and performers' actions. Some composers claim they just 'respond' to sound and compose 'with their ears', while others use models and analogies of previously 'non-musical' processes. It is evident that in such new musical practices the human body has a new relationship to the sound. There is a historical dimension to this, for since the earliest electroacoustic experiments in 1948 the body has been celebrated or sublimated in a strange 'dance' of forces in which it has never quite gone away but rarely been overtly present. The relationship of the body performing to the spaces around has also undergone a revolution as the source of sound production has shifted to the loudspeaker. Emmerson considers these issues in the framework of our increasingly 'acousmatic' world in which we cannot see the source of the sounds we hear. Contents: Preface and introduction: 'between disciplines'; Living presence; The reanimation of the world: relocating the 'live'; The human body in electroacoustic music: sublimated or celebrated?; 'Playing space': towards an aesthetics of live electronics; To input the live: microphones and other human activity transducers; Diffusion-projection: the grain of the loudspeaker; References; Index.
Keywords: 21st Century (2001-2100); Electronic music